The Practice of Tikrar Method in Memorizing the Quran Junior High School Students in Indonesia - Ahmad Muhammad Ath-Thukhi; Yelsi Budy Yana; Rida Sofiana; Anggi Afrina Rambe; Nasir Hassan Wani (Journal of Theory and Research Memorization Quran, 2025)
Quran memorization activities in Indonesia are of great interest to students. Many educational institutions have made Quran memorization one of the extracurricular activities and school flagship programs. However, one of the junior high schools in West Sumatra is different. This school makes a special class per level to memorize the Quran or called the tahfizh class. Graduates from this school can memorize at least 3 juz, some even more according to the ability of each student. In tahfidz learning, students use the tikrar method so that they are able to memorize the Quran and then maintain the memorization well. The purpose of this study was to determine the practice of implementing the tikrar method in memorizing the Koran. This research uses a qualitative method using a case study approach. Data sources were taken from eighteen informants through in-depth interviews. The eighteen informants consisted of the principal, tahfizh teachers and special students of tahfizh class. To obtain data, the author conducted observations, interviews and documentation. This study found that there are six stages of students using the tikrar method in memorizing the Quran, namely: reading verses by looking at the Mushaf, repeating verses by looking at the Mushaf, repeating verses without looking at the Mushaf, combining memorized verses with the next verse, tasmi' (reciting) memorization of the Quran to the teacher and murojaah or repeating memorization. This research can be used as a reference for educational institutions and teachers and guide students in memorizing the Quran.